c-FLIPL regulates endoplasmic reticulum morphology and mitochondria-associated membranes functions - Marini, Elettra Sara; Giampietri, Claudia; Petrungaro, Simonetta; Conti, Silvia; Scorrano, Luca; Ziparo, Elio (Italian Journal of Anatomy and Embryology, 2014)
Physical and functional interactions between endoplasmic reticulum (ER) and mitochondria take place at the mitochondria-associated membranes (MAMs), ER subdomains at the interface between the two organelles. Protein complexes at MAMs regulate lipid synthesis, Ca2+ signaling and apoptosis 1. Furthermore, they influence both ER and mitochondrial morphology, as their ablation is frequently associated to the dramatic remodeling of these organelles. Here we show that c-FLIPL (cellular FLICE-inhibitory protein, long isoform), mainly known as inhibitor of caspase-8, can be retrieved at the ER and MAMs. c-FLIP ablation in mouse embryonic fibroblasts (MEFs) impairs ER morphology and luminal contiguity, by inducing the proliferation of ER cisternae to the detriment of tubular ER. Furthermore, c-FLIPL controls the ER-mitochondria apposition, as the depletion of this protein physically uncouples the two organelles. Moreover, functionally, c-FLIP ablation lowers the cytosolic Ca2+-increase evoked either by agonists stimulation or by passive ER discharge and increases the resistance of c-FLIP-/- cells to ER stress-induced apoptosis. We also report that c-FLIP-/- cells show an increased caspase-mediated cleavage of the ER-shaping protein Reticulon-4 (which is a well-known regulator of ER biogenesis and morphology), at both basal level and upon TNFα-dependent apoptosis. In agreement with these findings, we finally show that c-FLIP absence enhances basal caspase-8 activation in c-FLIP-/- MEFs and that caspase-8 inhibition reverts morphological alterations in ER shape observed in c-FLIP-/- cells, suggesting a novel role for caspase-8 and c-FLIPL as regulators of ER functions and ER-mitochondria crosstalk.